Wina a wymiar kary wobec recydywistów w świetle doświadczeń niemieckiego prawa karnego - Janiszewski, Bogusław (Wydział Prawa i Administracji UAM, 1991)
The article investigates the problem of the possibility of relating the principle of guilt, as a basis of sentencing, to the offenders. This problems was considered in detail in the criminal law literature of the Federal Republic of Germany, especially in the light of presently repealed Art. 48 of the German Criminal Code. The solution of the above problem may be reached by means of compromise between guilt, which determines the upper level of penalty, also with respect to repeated offenders, and the requirements of prevention. Besides, the article considers the question of harmonising the factors of guilt and prevention in the light of the „technique" of modifying penal sanctions.
Guilt and penalty for repeated offenders in the light of experience of German criminal law